2014
DOI: 10.1590/2317-1782/20142014068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inter-judge agreement on perceptual judgment of nasality

Abstract: Descritoresbetween the two models. However, the second model showed a higher proportion of accuracy (7%) than the first one, and it has also predicted the borderline VP closure. Conclusion: These results showed the importance of high index of inter-judge agreement when using subjective parameters of speech evaluation, especially when compared to an instrumental evaluation. This suggests the need for strategies for training and calibration of judges in the perceptual judgment to improve the reliability of audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
2
7
0
5
Order By: Relevance
“…Similar to the present study, previous investigations also observed variable agreement between different listeners (12,16,17) . A study on hypernasality, based on three examiners with more than 10 years of experience with cleft lip and palate, revealed moderate agreement between them, evidencing that the result can be associated with related to internal standards of each examiner (12) .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to the present study, previous investigations also observed variable agreement between different listeners (12,16,17) . A study on hypernasality, based on three examiners with more than 10 years of experience with cleft lip and palate, revealed moderate agreement between them, evidencing that the result can be associated with related to internal standards of each examiner (12) .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the examiners' experience is a determining factor for the evaluation of results, indicating that an experienced examiner is more demanding in the analysis, which favors the accurate diagnosis of speech disorders. This highlights the importance of training and previous experience in the evaluation and treatment of cleft lip and palate (12) . The visual support from the videos is a variable that should be considered and which may have influenced the assessment by examiners.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations